Thermodynamic and kinetic description of the second order phase transitions - Klimontovich, Yu.L. (Condensed Matter Physics, 2000)
Thermodynamic and kinetic description of phase transitions for the model
of ferroelectrics based on the kinetic equation for the distribution function
of values of the “order parameter”, coordinates and time is considered.
For one-domain ferroelectrics, the self-consistent approximation for the ﬁrst
moment is used. The kinetic equation is reduced to the relaxation Ginsburg-
Landau equation. The susceptibility is governed by the Curie law and the
heat capacity has the jump.
Calculations are carried out for one-domain and polydomain ferroelectrics.
In the ﬁrst case, the self-consistent approximation for the ﬁrst moment is
used. In the second case, the self-consistent approximation for the second
moment is carried out. In the last case, there is the jump of the susceptibility. The heat capacity is governed by the Curie law.
It is also shown that the Ornstein-Zernike formula is valid not for the space
correlator of ﬂuctuations but only for the temporal spectral density of the
space correlator at zero frequency.
In the kinetic theory of the phase transition, all physical characteristics at
the critical point have got ﬁnite values. Thus, the problem of the “inﬁnities”
is absent. Проведено опис термодинаміки і кінетики фазових переходів моделі
сегнетоелектриків на основі кінетичного рівняння для функції розподілу, залежної від “параметра порядку”, координат і часу.
Для однодоменних сегнетоелектриків застосовано самоузгоджений
підхід до розрахунку першого момента. Кінетичне рівняння зводиться до релаксаційного рівняння Гінзбурга-Ландау. Сприйнятливість
описується законом Кюрі, а теплоємність має стрибок.
Розрахунки проведено для однодоменних та полідоменних сегнетоелектриків. У першому випадку використовується самоузгоджене
наближення для першого моменту. У другому випадку самоузгоджене наближення робиться для другого моменту. В цьому випадку відзначається стрибок сприйнятливості, а теплоємність описується законом Кюрі.
Показано, що формула Орнштейна-Церніке справедлива не для просторового корелятора флуктуацій, а лише для спектральної густини
цієї кореляційної функції при нульовій частоті.
В кінетичній теориї фазових переходів усі фізичні величини мають
скінчені значення в критичній точці. Таким чином, немає проблеми
“розбіжностей”.